Analisis Belt Conveyor Sabut dan Belt Conveyor Ampas di PT. XYZ - Muhammad Fadhlan Farris; Viktor Naubnome; Ratna Dewi Anjani (Jurnal Ilmiah Wahana Pendidikan, 2022)
In the industrial world, the belt conveyor is the most widely used material transfer tool. In addition to moving materials, conveyor belts also make human work more effective and efficient. This research is a quantitative study by direct observation to the field and analyzing the conveyor bell system. The result of this research is the maximum carrying capacity at PT. XYZ on the coir conveyor belt is 14618.9 kg/m, while the maximum capacity on the pulp conveyor belt is 46.932.48 kg/m3 and the motor power requirement at PT. XYZ to drive the coir conveyor belt is 10.4 kW, while the power requirement of the driving motor